Conditions for Investment in Genetic Biocontrol of Pest Vertebrates in Australia - Carter, Lucy; Mankad, Aditi; Campbell, Susan; Ruscoe, Wendy; Oh, Kevin P.; Brown, Peter R.; Byrne, Margaret; Tizard, Mark; Strive, Tanja (Frontiers in Agronomy, 2022)
Managing pest vertebrate species in Australia is a significant challenge for government, industry, research sectors and land-managers. Innovative tools such as genetic biocontrol offers decision-makers a potentially effective means of reducing the impact of pest species incursions. To determine the conditions for investment in genetic biocontrol, we applied qualitative engagement methodologies to identify and integrate existing knowledge of pest species research and management in Australia. Two facilitated workshops were held to determine key topics related to genetic biocontrol technologies for selected pest species. The topics explored during workshop discussions included: identifying existing knowledge gaps; risk perceptions; social and ethical considerations and; industry and business considerations. The workshops’ aim was to assess the potential, the priorities and the risk parameters among expert stakeholders and decision-makers for using genetic biocontrol approaches to reduce the impacts of key pest species in Australia. This paper reports on the design, process and outcomes of each workshop to inform the creation of a decision framework. Stakeholders were cautiously optimistic of pursuing continued research and development for vertebrate pest management in Australia. However, employing an appropriate, transparent process for incorporating diverse stakeholder perspectives on genetic biocontrol technologies is essential to ensure their development and use remains supported. This outcome will require meaningful investment in both social science investigations and well-considered engagement processes concurrent with biotechnology development globally.